2022
DOI: 10.32535/jicp.v5i5.2040
|View full text |Cite
|
Sign up to set email alerts
|

SMA-Technique Strategic Planning, Control and Performance Measurement in Village-Owned Enterprises in Indonesia

Abstract: https://www.ejournal.aibpmjournals.com/index.php/JICP When the development of organizational target strategies is based on the findings of organizational environmental analysis sstudies, BUMDes management is successful (Sriyono, Pujiastuti, Nugroho, & Soeprapto, 2021). BUMDes face opportunities and challenges in the field related to rapid competition and effective resource management. These are essential first steps that must be taken: developing, choosing, and implementing a business strategy. Information wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Research conducted by (Sriyono et al, 2022) explains that costing techniques using Strategic Management Accounting can be influenced by market orientation, which is influenced by the strategy used, while organisational size does not have a significant effect. Research by (Petera & Šoljaková, 2020) found that the most frequently used Strategic Management Accounting techniques are strategic planning and budgeting, customer accounting, and target costing.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by (Sriyono et al, 2022) explains that costing techniques using Strategic Management Accounting can be influenced by market orientation, which is influenced by the strategy used, while organisational size does not have a significant effect. Research by (Petera & Šoljaková, 2020) found that the most frequently used Strategic Management Accounting techniques are strategic planning and budgeting, customer accounting, and target costing.…”
Section: Introductionmentioning
confidence: 99%